Majallat al-Ibdāʿ and Arabic Vocabulary Enhancement: An Experimental Study - Muhammad Farid Shafaruddin; Yusuf Arisandi (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
Abstract Vocabulary acquisition remains a central challenge in Arabic language learning, particularly in non-Arabic speaking educational contexts. This study investigates the effectiveness of Majallat al-Ibdāʿ as a magazine-based instructional medium for enhancing Arabic vocabulary acquisition among senior high school students. A quasi-experimental pre-test–post-test control group design was employed, involving 60 third-grade students divided into experimental and control groups. The experimental group received structured vocabulary instruction through thematic integration of Majallat al-Ibdāʿ, while the control group was taught using conventional vocabulary teaching methods. Quantitative data were collected through standardized vocabulary tests measuring both receptive and productive vocabulary knowledge, and were analyzed using independent samples t-test and Cohen’s d effect size. Results revealed a statistically significant difference between the two groups (p < .01), with the experimental group demonstrating substantially higher vocabulary gains (M = 18.9) compared to the control group (M = 8.3). The calculated effect size (d = 1.45) indicated a large instructional impact. Qualitative findings further showed that students exposed to magazine-based instruction demonstrated deeper contextual usage and stronger semantic integration of newly learned vocabulary. These findings suggest that structured integration of thematic student magazines can serve as an effective and pedagogically viable strategy for vocabulary enhancement in Arabic language education. Keywords: Arabic vocabulary acquisition, magazine-based instruction, contextual learning